2017
DOI: 10.1152/ajpendo.00122.2017
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 regulates metabolic homeostasis in skeletal muscle through activation of AMPK

Abstract: Because of the mass and functions in metabolism, skeletal muscle is one of the major organs regulating whole body metabolic homeostasis. SIRT6, a histone deacetylase, has been shown to regulate metabolism in liver and brain; however, its specific role in skeletal muscle is undetermined. In the present study we explored physiological function of SIRT6 in muscle. We generated a muscle-specific SIRT6 knockout mouse model. The mice with SIRT6 deficiency in muscle displayed impaired glucose homeostasis and insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 43 publications
0
64
2
Order By: Relevance
“…The expression of PGC-1α is regulated by a series of proteins (NOS, P38, ERK1/2, Akt, CaN, CaMK, CDK, AMPK) [41,42], among which nitric oxide synthase (NOS) [43], adenylate-activated protein kinase (AMPK) [44], Akt [45] and ERK1/2 [46] are regulated by Sirt6. Our results showed that the NOS inhibitor L-NAME did not affect the expression of PGC-1α induced by Sirt6, but the AMPK inhibitor Comp C not only blocked the effect of Sirt6 on PGC-1α but also promoted the mtDNA damage, ROS accumulation, and MDA upregulation induced by GCDC.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PGC-1α is regulated by a series of proteins (NOS, P38, ERK1/2, Akt, CaN, CaMK, CDK, AMPK) [41,42], among which nitric oxide synthase (NOS) [43], adenylate-activated protein kinase (AMPK) [44], Akt [45] and ERK1/2 [46] are regulated by Sirt6. Our results showed that the NOS inhibitor L-NAME did not affect the expression of PGC-1α induced by Sirt6, but the AMPK inhibitor Comp C not only blocked the effect of Sirt6 on PGC-1α but also promoted the mtDNA damage, ROS accumulation, and MDA upregulation induced by GCDC.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 was found necessary for induction of SIRT6 in mouse liver during the unfed period (23), and deletion of SIRT6 in mouse muscle reduced whole‐body insulin sensitivity (27). In the present study, SIRT1 protein content and activity was increased with the hypercaloric saturated HFD without concomitant change in SIRT6 protein content, suggesting that SIRT1 activation is not sufficient to induce SIRT6 protein content in human skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Whole body deletion of SIRT6 causes 60% mice death around 4 weeks owning to hypoglycemia (Xiao et al, 2010). Nevertheless, the skeletal muscle-specific knockout of SIRT6 causes insulin resistance and impairs glucose homeostasis of mKO mice (Cui et al, 2017). Because the activity of AMPK is reduced in SIRT6-mKO mice, the glycolipids absorption and utilization of skeletal muscles are impaired, and the exercise capacity of the mice was also attenuated (Cui et al, 2017).…”
Section: Sirt6 Improves Muscle Fitness and Exercise Capacitymentioning
confidence: 99%